Ink protection of security documents - Mansour, Saleh (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Security documents are valuable documents protected by a mixture of security features, starting from security paper, inks, printing techniques, and additional security properties. However, this article will discuss the main security features, supported by genuine and forged examples, to demonstrate the most frequent modern use of security features to protect valuable documents, and giving useful hints to detect forgeries and imposters as well.
Keywords: dokumenty zabezpieczone; techniki druku; sfałszowane dokumenty; druk offsetowy; druk płaski; typografia; cechy bezpieczeństwa; atramenty bezpieczne; farby zabezpieczające; zabezpieczenie dokumentu; druk wklęsły; sitodruk